Inhalation of phlai-containing essential oil enhances cognition: a comparison with olive oil in healthy adults - Gomonchareonsiri, Sumittra; Arpornchayanon, Warangkana; Chansakaow, Sunee; Varnado, Pairada; Wongpakaran, Nahathai; Wongpakaran, Tinakon (Frontiers in Pharmacology, 2026)
Background/ObjectivesPhlai (Zingiber montanum and Zingiber tenuiscapus), traditionally valued for its anti-inflammatory properties, has potential applications as a functional ingredient in sustainable food systems. However, its effects on cognitive function are not well understood. This study investigates the acute cognitive effects of inhaling Phlai-containing essential oil in healthy adults, aiming to explore its potential as a basis for developing plant-based cognitive enhancers within the context of nutritional sustainability.MethodsA double-blind, randomized, controlled trial was conducted with 40 healthy male volunteers. Participants were assigned to either an olive oil group (n = 20) or an essential oil blend (ESOB) group (n = 20), with Phlai as the primary component. Each participant inhaled a single dose of their respective essential oil for 15 min. Cognitive performance was assessed before and after the intervention using the Montreal Cognitive Assessment (MoCA), the Digit Span Test, the Verbal Fluency Test (VFT), and the Word List Learning Test (WLL). Differences in cognitive outcomes between groups were analyzed using one-way ANCOVA, with a focus on working memory, short-term memory, retrieval fluency, executive function, and global cognition.ResultsBoth olive oil and ESOB inhalation resulted in measurable acute improvements in several cognitive domains. Notably, the ESOB Phlai produced significantly greater enhancements in working memory and executive function compared to olive oil. These findings highlight ESOB Phlai’s promise as a functional botanical ingredient with cognitive benefits, suggesting its future value in the development of sustainable, plant-based functional foods or nutraceuticals.ConclusionSingle-dose inhalation of a Phlai-containing essential oil may acutely enhance cognitive function in healthy adults, supporting the consideration of Phlai as a sustainable, plant-derived ingredient for functional food systems. Further research is warranted to confirm these findings and to investigate practical applications within the food and nutrition sector.Clinical Trial Registrationhttps://www.thaiclinicaltrials.org/show/TCTR20180710008, identifier TCTR20180710008.